Projecting the Mobility of School Teachers of Islamic Subject From Indonesia to Malaysia, Brunei Darussalam, and Thailand in the Era of Asean Free Market - Achmad Zaini; Ali Mas’ud; Ah Zakki Fuad (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2021)
This article deals with mapping of teacher’s competence for Islamic religious subject in facing ASEAN Economic Community. Since the free market has launched in 2015, ASEAN countries will transform to be a region in which goods, services, skilled workers and capital can move freely. It means that all skilled workers, including teachers of Islamic subjects, have the same access to get a good job suitable with their competence in ASEAN countries. To prepare such skilled workers, it is very important to understand and to map the competences standard of Islamic religious teacher set up by Islamic education institutions (schools) in ASEAN countries.We conclude that there are at least two basic competences and five additional competences required. Two basic competences are mastery of Islamic teachings (theology and law) and good command in Arabic, both written and spoken (muhadathah). While five additional competences are mastering local languages (Malay and Thai); English; writing and reading Malay-Arabic script (Arab-Jawi);performing Islamic rituals with a special reference to Shafi‘i’s school of thought; and computer literacy. To compete and to fulfill the demand of the above competences, it is needed to make sure that the implementation of the curriculum of Islamic Education Department in the Faculty of Islamic Education in Indonesian Islamic higher education has been going well, and to adopt as well as to change it as long as in line with the competences needed.